Convert the equation to the standard form for a hyperbola by completing the square on x and y. x2 - y2 + 6x - 4y + 4 = 0?
(x + 3)2 + (y + 2)2 = 1


(x + 3)2 - (y + 2)2 = 1


(y + 3)2- (x + 2)2 = 1


(y+3)^2/16 − (x+2)^2/36 = 1

Answers

X² + 6x + ____ - (y² + 4y + ____ ) = -4 + ____ + ____ x² + 6x + 9      -  (y² + 4y + 4 )       = -4 +   9     +    -4    (x + 3)²        -      (y + 2)²            = 1 Answer: B


0 0
Only authorized users can leave an answer!
Can't find the answer?

If you are not satisfied with the answer or you can’t find one, then try to use the search above or find similar answers below.

Find similar answers


More questions